Ecological Consciousness in John Steinbeck’s Tortilla Flat: An Ecocritical Reading - Dhungel, Bharat (Mindscape: A Journal of English & Cultural Studies, 2025)
This paper explores ecological consciousness in John Steinbeck’s Tortilla Flat through the lens of ecocriticism. Although the novel has often been interpreted as a light-hearted and comic tale of paisanos living in post-war Monterey, this study argues that beneath its humor lies a profound ecological vision. Steinbeck portrays characters whose lives are closely tied to the land, the sea, and other living beings, thereby suggesting that human existence cannot be separated from the natural world. Drawing on the theoretical perspectives of Aldo Leopold, Paul Taylor, and other ecocritics, the research emphasizes three key aspects: the holistic interconnectedness between humans and nature, the significance of simple and sustainable lifestyles, and the reverence for the natural environment. The communal life of the paisanos characterized by sharing, closeness to the land, and respect for nonhuman beings illustrates principles of deep ecology and biocentrism. At the same time, their rejection of materialism and pursuit of contentment through community and nature subtly challenges the anthropocentric values that dominate modern industrial societies. Methodologically, the study is based on close textual analysis of Steinbeck’s novel, supported by critical readings in ecocriticism. The findings suggest that Tortilla Flat anticipates many concerns of contemporary ecological thought, offering valuable insights into how literature can shape ethical attitudes toward sustainability, environmental harmony, and ecological justice.